2012
DOI: 10.1086/662137
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Unilateral Divorce on Crime

Abstract: The Impact of Unilateral Divorce on Crime * In this paper, we evaluate the impact of unilateral divorce on crime. First, using crime rates from the FBI's Uniform Crime Report program for the period 1965-1998 and differences in the timing in the introduction of the reform, we find that unilateral divorce has a positive impact on violent crime rates, with an 8% to 12% average increase for the period under consideration. Second, arrest data not only confirms the findings of a positive impact on violent crime but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…The findings from this study provide evidence in support of the turning point hypothesis and complement recent studies exploiting natural experiments to estimate the effects of marriage on crime (Caceres-Delpiano and Giolito 2008; Edlund et al 2007). The findings also inform the relatively recent literature on the effects of incarceration on child and family well-being (e.g., Geller et al 2009; Wildeman 2009, 2010) by underscoring the potential importance of reverse pathways.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The findings from this study provide evidence in support of the turning point hypothesis and complement recent studies exploiting natural experiments to estimate the effects of marriage on crime (Caceres-Delpiano and Giolito 2008; Edlund et al 2007). The findings also inform the relatively recent literature on the effects of incarceration on child and family well-being (e.g., Geller et al 2009; Wildeman 2009, 2010) by underscoring the potential importance of reverse pathways.…”
Section: Resultssupporting
confidence: 85%
“…From difference-in-difference models, the authors found that (1) the one-child policy increased the sex ratio in China, so that by 2004, there were about 1.1 males per female in the 16–25 age cohort compared with a ratio of less than 1.06 in 1986; (2) a 0.01 increase in the sex ratio increased both violent and property crime rates by about 3%; and (3) the increases in crime were due not only to the relative increase in the male population but also to declining marriage rates among men. Caceres-Delpiano and Giolito (2008) examined the impact of unilateral divorce laws in the United States on state-level aggregate arrest rates between 1965 and 1998. Using difference-in-difference models, the authors found evidence that unilateral divorce laws increased arrests for both violent and property crimes among men aged 20 to 24 years.…”
Section: Introductionmentioning
confidence: 99%
“…This same identifying variation leads Cáceres‐Delpiano and Giolito () to conclude that individuals who were children at the time of the reforms exhibited higher rates of violent crime arrests as adults. Both Antecol and Bedard () and Cáceres‐Delpiano and Giolito () cite reduced supervision and adult interaction as possible mechanisms. We believe this explanation to be particularly relevant for athletes as coaches have the potential to serve as de facto surrogates to active athletes, providing adult supervision and role modeling otherwise absent.…”
mentioning
confidence: 88%
“…For instance, a 2004 study finds that children who grew up in US states that allowed unilateral divorce had fewer years of education and lower family income (as adults) than did children raised in states that did not allow unilateral divorce [8]. A more recent study also finds that children who were young when unilateral divorce became available were more likely to commit violent crimes later in life, resulting in higher crime rates ten years after the reforms in states that introduced unilateral divorce [9]. The study attributes this effect to an increase in poverty among divorced mothers affected by the reforms.…”
Section: Childrenmentioning
confidence: 99%